Attitudes toward tax evasion: a comparative study of France and Japan. (30th June 2021) - McGee, Robert W.; Souissi, Mohsen; Tadros, Hani
This study investigates how cultural dimensions such as individualism and uncertainty avoidance account for differences in attitudes toward tax evasion between Japan and France. It also looks into another important moderating factor, namely gender that may explain these differences. Informed by Hofstede's cultural framework (1980), the study consists of a survey built around historical arguments provided in the literature, that were used to explain and justify tax evasion. We collected data by surveying 154 university students from Japan and 61 students from France. An ANOVA was used to test for differences in attitudes toward tax evasion between the two samples. The results of the study are in line with the extant literature. French students, internalising a higher degree of individualism and lower level of uncertainty avoidance, were more opposed to tax evasion than their Japanese counterparts. Moreover, the findings of the study confirm that women are generally more conservative by exhibiting stronger opposition to tax evasion than men in the French sample.